2020
DOI: 10.1186/s40538-019-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the passive cuticular membrane permeability of potassium with a parallel artificial membrane permeability assay and the implications for foliar nutrient formulations

Abstract: A modified PAMPA (parallel artificial membrane permeability assay) is proposed for evaluating the passive cuticular membrane permeability of potassium in several foliar nutrient formulations. The modified PAMPA can measure the passive permeability of ionic nutrients under fully hydrated conditions through an artificial membrane designed to more closely resemble a plant cuticle, rather than the traditional phospholipid animal model. Foliar nutrient formulations, which in some cases contain a complex organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Additionally, drug carriers based on SA have been reported to improve the solubility of hydrophobic drugs [55,56] and inhibit the photodegradation of active compounds such as imidacloprid [57]. Adjuvants may also enhance permeability through insect cuticular waxes, similar to mechanisms allowing for increased ion permeability through the leaf cuticle [58]. The cuticular waxes between P. guildinii and L. lineolaris may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, drug carriers based on SA have been reported to improve the solubility of hydrophobic drugs [55,56] and inhibit the photodegradation of active compounds such as imidacloprid [57]. Adjuvants may also enhance permeability through insect cuticular waxes, similar to mechanisms allowing for increased ion permeability through the leaf cuticle [58]. The cuticular waxes between P. guildinii and L. lineolaris may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular penetration and the effect of several chemicals including ions, solvents, and surfactants on CM have been studied for over four decades [ 18 ]. Review of the literature into permeability studies through the plant cuticle indicated that the majority of these studies often included the interaction of individual chemicals [ 19 ] or individual chemical with single surfactants [ 20 ] with cuticular membranes. On the other hand, commercial surfactants like the ones that are used in this research are often combination of two or more chemicals, a typical end user product that has not been investigated.…”
Section: Introductionmentioning
confidence: 99%